2022
DOI: 10.1111/chso.12562
|View full text |Cite
|
Sign up to set email alerts
|

‘Childhood in the shadow of prison bars’: How school counselors cope while counseling children of incarcerated parents

Abstract: This qualitative study examines how school counsellors perceive children aged 14-18 whose fathers are incarcerated. Three main themes emerged from the in-depth, semi-structured interviews: (1) The school counsellors perceived feelings of vulnerability, shame, anger and lack of trust amongst the adolescents. (2) The father's incarceration was a turning point in the lives of families and served as a catalyst for major economic decline, forcing the adolescents to fend for themselves. (3) The school counsellors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The literature points to a high rate of exposure to trauma among children who have been in foster care (Kaasboll et al, 2019; Salazar et al, 2013). A recent study suggested that school counsellors should receive proper professional training on the topic of trauma (Levkovich & Ne'emani, 2022; Levkovich & Vigdor, 2020). Such training can enable them to develop a comprehensive counselling program for identifying, assessing and treating f students with post‐trauma (Martinez Jr et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The literature points to a high rate of exposure to trauma among children who have been in foster care (Kaasboll et al, 2019; Salazar et al, 2013). A recent study suggested that school counsellors should receive proper professional training on the topic of trauma (Levkovich & Ne'emani, 2022; Levkovich & Vigdor, 2020). Such training can enable them to develop a comprehensive counselling program for identifying, assessing and treating f students with post‐trauma (Martinez Jr et al, 2020).…”
Section: Discussionmentioning
confidence: 99%